The Body of the Courtesan, the Body of the Novel: Characterizing La Dame aux camélias and A la recherche du temps perdu through Marguerite Gautier and Odette Swann - Bruhn, Maury (Dalhousie French Studies, 2021)
As the work of critic Michael Finn has demonstrated, while Marcel Proust has a generally dismissive attitude towards the work of Alexandre Dumas fils, the latter’s character Marguerite Gauthier nonetheless inspired Proust’s portrayal of Odette Swann in A la recherche du temps perdu. This article builds on the work of Finn to establish narrative and character parallels between Proust’s novel and Dumas fils’ La Dame aux Camélias, and proposes that, given these clear resemblances, closely examining the ways in which Odette differs from Marguerite will help us understand the stylistic specificities of these novels. I ultimately argue that the portrayal of these courtesan figures echoes the formal properties of the novels themselves. Dumas fils’ novel and the character of Marguerite tend towards epistemological clarity and certainty, whereas Proust’s novel, and the character of Odette, reveal an open and heterogenous literary universe.